Uma contribuição didática do uso do lúdico para o processo de ensino-aprendizagem de química orgânica: um estudo de caso no curso de Tecnologia Mecânica na modalidade Produção Industrial de Móveis da UDESC - Planalto Norte - Campos, Débora Barni de (2009)
This dissertation presents a suggestion of using the pedagogy methodology with playful appeal to the teaching of organic chemistry in higher education. The theoretical framework guiding this study is the Theory of Meaningful Learning by David Ausubel and the Theory of Social-Interactionist by Vigotsky. It was performed a comparative research between expositive methodology and playful-educational methodology, with the development of playful kit innovated of the games: ''Organic Chemistry Domino'', ''Organic Chemistry Game Board'', ''Macro Molecular Models'', and ''Organic Chemistry Memory''. 30 students from first degree of Mechanic Tecnology career of Santa Catarina University, of the Education Center of the Northern Plains, situated in São Bento do Sul - SC had participated of the experiments. The results showed the average improvement in the discipline in comparison to previous semesters in which expositive classes were given. It is concluded that the method of playful develops the autonomy granted to the development of subjectivity, expansion of the powers of initiative, creative ability, skill, teamwork, planning, assimilation and resolution of problems.